Active galactic nuclei : fueling and feedback - Combes, F. (IOP (Series). Release 21., 2021)
Almost all galaxies host in their center a supermassive black hole of mass between a million and tens of billions solar masses. Supermassive black holes grow in symbiosis with their host galaxies across the Hubble time, occasionally accreting surround matter, giving rise to an Active Galactic Nuclei (AGN). This book gives a general review of our current knowledge of AGN, powered by supermassive black holes: how they are fueled by gas (or stars) and what problems are encountered; how can we account for the wide variety of AGN, from Seyfert/Liners to quasars, and for the two types (AGN 1 and 2) either through dust obscuration, and geometrical orientation arguments, or through intrinsic activity difference, qualitative or quantitative.